2018
DOI: 10.1186/s13195-018-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive composite score association with Alzheimer’s disease plaque and tangle pathology

Abstract: BackgroundCognitive composite scores are used as the primary outcome measures for Alzheimer’s disease (AD) prevention trials; however, the extent to which these composite measures correlate with AD pathology has not been fully investigated. Since many on-going AD prevention studies are testing therapies that target either amyloid or tau, we sought to establish an association between a cognitive composite score and the underlying pathology of AD.MethodsData from 192 older deceased and autopsied persons from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Traditional NP tests in common among the three neuroimaging studies include the Mini Mental State Exam (MMSE), Wechsler Memory Scale Revised (WMS‐R) Logical Memory Story A immediate and delayed recall, semantic fluency (animals), Trail Making Tests A & B, and clock drawing 29,30 . Traditional NP test data were analyzed as raw scores, with the exception of two standardized composite scores, a processing speed composite (comprising Trail Making Tests and semantic fluency), and a global composite (comprising all seven traditional NP variables), following published methods 31 …”
Section: Methodsmentioning
confidence: 99%
“…Traditional NP tests in common among the three neuroimaging studies include the Mini Mental State Exam (MMSE), Wechsler Memory Scale Revised (WMS‐R) Logical Memory Story A immediate and delayed recall, semantic fluency (animals), Trail Making Tests A & B, and clock drawing 29,30 . Traditional NP test data were analyzed as raw scores, with the exception of two standardized composite scores, a processing speed composite (comprising Trail Making Tests and semantic fluency), and a global composite (comprising all seven traditional NP variables), following published methods 31 …”
Section: Methodsmentioning
confidence: 99%
“…There is a recent surge in composites derived from batteries of tests in AD research 5 . They have been developed for multiple purposes, including sensitivity to global disease severity, 32 individual cognitive domains, 2,3 or longitudinal change 33 —particularly in the preclinical phase relevant to secondary prevention trials 34 . In their recent review, Schneider and Goldberg 5 identified 12 composite scales that have been used in clinical trials to assess cognitive functions.…”
Section: Perspectivesmentioning
confidence: 99%
“…To confirm that the Tau tracers were binding to regions containing Tau, AT8 immunostaining was performed on adjacent sections at Barrow Neurological Institute. Paraffin-embedded sections were deparaffinized and pre-treated for antigen retrieval using formic acid, as previously described [ 12 ]. Endogenous peroxidase activity was blocked by 1% hydrogen peroxide, followed by incubation overnight with the AT8 monoclonal antibody (1:1000, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%